PELATIHAN DAN PENDAMPINGAN STRATEGI PEMASARAN DALAM MEMPERLUAS PANGSA PASAR DI INDONESIA TIMUR DAN PERHITUNGAN BIAYA POKOK PRODUK PADA UMKM DI KAB. KEDIRI - Andarwati, Andarwati (FKIP Universitas Wisnuwardhana, 2024)
This community service activity aims to provide training and assistance related to how to determine marketing strategies in expanding market share to the Eastern Indonesia region and calculating product costs for MSMEs in Kediri Regency. The MSMEs that are guided are focused on MSMEs engaged in snacks that are in high demand in the market. Based on the results of initial communication with prospective partners, namely small and medium business actors in the city of Kediri, where these small business actors do not yet understand the importance of determining the right marketing strategy to support the development of their business. Business actors only do marketing in conventional or traditional ways. This will certainly be a definite obstacle for MSMEs because with this method, consumers are only limited to the community around the MSME area. So the solution offered is to provide training and assistance in determining marketing strategies in expanding market share and calculating product costs for MSMEs in Kediri Regency. The results of this training and assistance are that the participants better understand and are able to apply how to determine marketing strategies that are in accordance with the business they are running and the participants also better understand the importance of calculating production costs for the sustainability of their business.